3D Collaborative Virtual Environment based e-learning system. (13th July 2010) - Lin, Qingping; Zhang, Liang; Ding, Sun; Wang, Weihua; Neo, Ker; Gay, Robert
3D visualisation plays an important role in understanding abstract and complex concepts. In this paper, we move one step further by proposing a 3D multiuser collaborative virtual environment (CVE) system for e-learning. It provides an engaging learning environment, where the students and lecturers can collaboratively interact with the 3D e-learning contents, which will response based on law of physics or simulation rules. This would be particularly useful for those subjects that require multiuser collaboration. It also bridges the gap between lecturers and students by providing virtual real-time interactions, thus overcoming the limitations resulted from the distance issue in the Distance Learning.